Performance of Jute-Based Cropping Systems under Mung Bean and Cowpea Intercropping in Rainfed Conditions - Tripathi, Santosh Raj; Rijal, Tirtha Raj; Karki, Sujan (Agronomy Journal of Nepal, 2025)
Jute productivity in South Asia faces challenges due to declining soil fertility, heavy weed problems, and increasing production costs. Legume intercropping provides a sustainable approach by improving nutrient availability, controlling weeds, and increasing overall productivity. This three-year field experiment from 2022 to 2024 was conducted at the Jute Research Program in Itahari, Nepal. It aimed to evaluate the impact of mung bean and cowpea intercropping on the growth, fiber yield, and economic returns of three tossa jute varieties: Itahari-4, JRO-204, and NJ-7010. The experiment used a split-plot design with legumes planted between jute rows. Intercropping notably affected most growth and yield parameters, while the differences among varieties were mostly insignificant. Cowpea (Malepatan-1) and mung bean (Local) enhanced plant height, basal diameter, and biomass production compared to sole cropping. In combined analysis, the highest green plant yield (58.79 t ha⁻¹), green fiber yield (21.63 t ha⁻¹), and dry fiber yield (3.90 t ha⁻¹) were found in jute + cowpea (Malepatan-1), showing increases of 35% to 60% over sole cropping. The intercrop yield equivalent to jute fiber reached 1.0 to 1.56 t ha⁻¹, making a significant contribution to total productivity. The Jute Fiber Equivalent Yield (JFEY) was highest in jute + cowpea (Malepatan-1) at 5.40 t ha⁻¹, more than double the yield from sole cropping. Economic analysis showed net returns up to Rs. 520,391 ha⁻¹ for jute + cowpea (Malepatan-1) compared to Rs. 248,500 ha⁻¹ for sole jute. Overall, cowpea (Malepatan-1) proved to be the most compatible intercrop, offering substantial yield and economic benefits across jute varieties. The findings confirm that intercropping with legumes, especially cowpea, greatly improves productivity, profitability, and sustainability in jute farming systems in Nepal.